DISTRIBUTION OF EPSTEIN - BARR VIRUS AMONG WOMEN OF REPRODUCTIVE AGE AND CHILDREN UP TO 1 YEAR IN THE VARNA REGION - Tsvetelina Kostadinova; Liliya Ivanova; Denitsa Tsaneva; Neli Ermenlieva; Zhivka Stoykova; Gabriela Tsankova (Peytchinski Publishing, 2019)
Purpose: The Epstein-Barr virus (EBV) is widespread in the human population and is the major cause of infectious mononucleosis. Also, the virus is associated with the development of Hodgkin's and non-Hodgkin's lymphomas and nasopharyngeal carcinoma. The evidence of its role in neonatal pathology is contradictory and not well known. The aim of this study is to evaluate the EBV serostatus of women of reproductive age in the Varna region (2010-2016) to determine the risk of intrauterine and early postnatal EBV infection. Materials/Methods: We analyzed the results of a total of 1126 women of reproductive age and 360 children up to 1 year tested for anti-VCA IgM (viral capsid antigen) and anti-VCA IgG. An indirect ELISA of Euroimmun - Germany was used. Results: The proportion of positive anti-VCA IgG women in the reproductive age (76.8%; 95% CI: 74.2 %-79.3%) correlates with that of children up to 6 months - 68.0% (95% CI: 62.1% -73.6%), Pearson's = 8.395, p = 0.004. Conclusion: We found high anti-VCA IgG seropositivity among women of reproductive age, which reduces the risk of infection during pregnancy and intrauterine infection of the fetus, respectively. The presence of seronegative women (around 6.0%) and of women with serological evidence of primary infection or reactivation (17%) assumes a group of babies at risk of early infection. Despite the little evidence of virus involvement in neonatal pathology, contamination should be considered and sought after excluding the most common infectious agents.